TEACHER PERSONALITY COMPETENCIES AS CHARACTER MODEL OF ELEMENTARY SCHOOL STUDENTS - Marlina Eliyanti; Yogi Kuncoro Adi; Shamira Angraeni; Dhea Putri Pratiwi (The University of Kuningan, 2021)
This research was conducted because of the many cases that occurred regarding moral decline committed by teachers as educators. The formulation of the problem in this study is how the teacher's personality competence is an example of the character of elementary school students. The purpose of this study was to describe the personality competencies of teachers as character models of elementary school students. The research method used was a survey with quantitative descriptive analysis. To collecting data, we used closed and open-ended questionnaires. The sample of this study used non-probability volunteer sampling with a total of 94 teachers and 344 students as respondents. To validating the instrument, we used expert judgment. This research data analysis using descriptive analysis. The results of this study indicate that: the teacher's personality competence is in the very high category. This proves that the teacher has mastered the aspects of personality competencies that must be possessed by the teacher. Through the teacher's mastery of the teacher's personality competence, it shows that the teacher has a very important role to develop the character of elementary school students.